(untitled) (Ibrahim Cardiac Medical Journal, 2022)
Background & objective: Obesity is rapidly emerging as one of the major causes of non-alcoholic fatty liver disease (NAFLD), the early sign of which is elevated liver enzymes. But very few studies have yet been done in our country to find the association between overweight and obesity and levels of serum hepatic enzymes. The present study was undertaken to determine the association between overweight/obesity determined by body mass index (BMI) and serum hepatic enzymes. Methods: This cross-sectional analytical study was conducted in the Department of Physiology, Rajshahi Medical College, Rajshahi over a period of one year between July 2018 to June 2019 in collaboration with the Department of Biochemistry of the same Medical College. Based on certain predefined enrolment criteria, 33 overweight or obese (BMI ≥23 kg/m2) individuals (case) and 33 sex-matched apparently healthy adults (BMI <23 kg/m2) (control) were included from the Rajshahi City. All the study subjects were then tested for serum hepatic enzymes (ALT, AST, ALP and GGT). The investigation findings obtained were compared between case and control groups. Result: The mean ages of the cases and controls were almost similar (31.1 and 29.4 years respectively, p = 0.576).All the serum hepatic enzymes but GGT were found to be significantly raised in the case group than those in the control group. The BMI was found to bear significantly linear relationship with serum ALT, AST and ALP (r = 0.709, p < 0.001, r = 0.718, p < 0.001 and r = 0.545, p < 0.001 respectively) indicating that more than 70% of the variations in ALT and AST and 55% of the variations in ALP might be due to variation in BMI. When waist circumference was correlated with hepatic enzymes, it was found to correlate better than the BMI did with 70.3% of the variations in ALT, 77.2% of variations in AST and 57.4% variation in ALP being explained by waist circumference. However, WHR did not correlate well with hepatic enzymes. AST alone bears a weekly significant correlation with WHR, with only 28% of the variations in AST could be explained by WHR. Conclusion: The study concluded that all the serum hepatic enzymes but GGT are significantly raised in the overweight and obese individuals than those in individuals with normal BMI. The BMI bears significantly linear relationships with serum ALT, AST and ALP. A substantial proportion of the variations in ALT and AST could be explained by BMI. Waist circumference correlates even better than the BMI does. However, WHR is not a good predictor of serum hepatic enzymes. Ibrahim Card Med J 2021; 11 (1): 62-70